Corporate Governance, Performance, Corporate Value, and Sustainability Reporting: A Systematic Literature Review - Kristiani, Wina; Djaddang, Syahril; Widyastuti, Tri (Jurnal Ar Ro'is Mandalika (Armada), 2026)
This study aims to analyze the influence of corporate governance, corporate performance, and corporate value on sustainability reporting in companies listed on the Indonesia Stock Exchange (IDX). The phenomenon of increasing awareness of sustainability issues and the demand for public transparency has driven companies to present sustainability reports as a form of social and environmental accountability. Although the adoption of sustainability reporting has become more widespread, its quality and consistency still vary, making it important to review the factors influencing these reporting practices. The research method used is a descriptive qualitative approach with a systematic literature review of various academic articles from the period 2020–2025. Analysis was carried out using thematic and comparative approaches to examine the relationships between variables based on previous research findings. The study's results show that corporate governance (Good Corporate Governance) has a positive impact on the quality of sustainability reporting through increased transparency and managerial oversight. Corporate performance also positively influences sustainability reporting, as companies with high profitability and efficiency have a greater capacity to implement and report sustainability activities. Meanwhile, corporate value is positively related to sustainability reporting, where sustainability reporting serves as a signal of trust for investors and the public, while enhancing the company's image and reputation. Overall, this research confirms that corporate governance, performance, and value play complementary roles in driving credible sustainability reporting practices. Academically, it enriches the literature on the integration of governance, performance, and firm value aspects in the context of corporate sustainability, while practically, the findings encourage public companies to strengthen governance systems and expand sustainability disclosures as a strategy for long-term value enhancement.